2006
DOI: 10.1002/jssc.200500304
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of arsenic by ion chromatography inductively coupled plasma mass spectrometry using ammonium eluents

Abstract: Original PaperSpeciation of arsenic by ion chromatography inductively coupled plasma mass spectrometry using ammonium eluents A method based on ion chromatography (IC) and inductively coupled plasma MS (ICP-MS) was developed for the speciation of arsenic in water and soil extracts. An anion-exchange column (G3154A/101) was used to separate As(III), As(V), dimethylarsinic acid (DMA), and monomethylarsonic acid (MMA) with excellent resolution. Various ammonium salts, including NH 4 H 2 PO 4 , (NH 4 ) 2 HPO 4 , (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…For a direct inlet into the ICP MS at 1 mL/min, phosphate concentration should clearly be lower than 15 mmol/L since at this concentration a rapid damage of expensive cones [159] and a drop in sensitivity due to clogging [160] was reported. Recently it has been shown that ammonium instead of Na-salts in the plasma produce less deposits [161]. Eluent splitting before the instrument inlet was used too in order to reduce the P-load.…”
Section: Selective Separation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a direct inlet into the ICP MS at 1 mL/min, phosphate concentration should clearly be lower than 15 mmol/L since at this concentration a rapid damage of expensive cones [159] and a drop in sensitivity due to clogging [160] was reported. Recently it has been shown that ammonium instead of Na-salts in the plasma produce less deposits [161]. Eluent splitting before the instrument inlet was used too in order to reduce the P-load.…”
Section: Selective Separation Methodsmentioning
confidence: 99%
“…Hence, approaching pH 7, phosphate is much more ionized which drastically increases its eluent strength. This was used to selectively increase the t R of DMA (pK a = 6.1) while the t R of other species remained [161]. Further deprotonation at higher pH, however, counteracts the selectivity among other As-species since the increased negative charge on phosphate shortens t R of arsenicals [157,161].…”
Section: Selective Separation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphate shares many similar chemical properties to arsenate, such as ion size and acid dissociation constants, and provides a mild extraction medium similar to environmental conditions . Therefore, ammonium phosphate buffer was selected as the primary extractant for arsenic extraction from soils in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the papers published on arsenic speciation in the past few years used (HPLC) as the basis of separating the species [108], this is usually coupled with mass spectra detector [109,110], (HG) [111], sensitive optical spectroscopic detection system such as (AFS) [112], (AAS) [113,114], (ICP-MS) [115], ion-pair reversedphase chromatography (IP-RP-HPLC) [116,117], and (IE-HPLC) [118,119]. That most studies agree with the use of HPLC which provided high efficiency of separation for very low concentration of the arsenic species, many of researchers agreed to couple (HPLC) with (ICP-MS) for measurement.…”
Section: 7 Ion Analysis (Hplc) Componentsmentioning
confidence: 99%